Silencing of Anopheles stephensi Heme Peroxidase HPX15 Activates Diverse Immune Pathways to Regulate the Growth of Midgut Bacteria - Kajla, Mithilesh; Choudhury, Tania P.; Kakani, Parik; Gupta, Kuldeep; Dhawan, Rini; Gupta, Lalita; Kumar, Sanjeev (Frontiers in Microbiology, 2016)
Anopheles mosquito midgut harbors a diverse group of endogenous bacteria that grow extensively after the blood feeding and help in food digestion and nutrition in many ways. Although, the growth of endogenous bacteria is regulated by various factors, however, the robust antibacterial immune reactions are generally suppressed in this body compartment by a heme peroxidase HPX15 crosslinked mucins barrier. This barrier is formed on the luminal side of the midgut and blocks the direct interactions and recognition of bacteria or their elicitors by the immune reactive midgut epithelium. We hypothesized that in the absence of HPX15, an increased load of exogenous bacteria will enormously induce the mosquito midgut immunity and this situation in turn, can easily regulate mosquito-pathogen interactions. In this study, we found that the blood feeding induced AsHPX15 gene in Anopheles stephensi midgut and promoted the growth of endogenous as well as exogenous fed bacteria. In addition, the mosquito midgut also efficiently regulated the number of these bacteria through the induction of classical Toll and Imd immune pathways. In case of AsHPX15 silenced midguts, the growth of midgut bacteria was largely reduced through the induction of nitric oxide synthase (NOS) gene, a downstream effector molecule of the JAK/STAT pathway. Interestingly, no significant induction of the classical immune pathways was observed in these midguts. Importantly, the NOS is a well known negative regulator of Plasmodium development, thus, we proposed that the induction of diverged immune pathways in the absence of HPX15 mediated midgut barrier might be one of the strategies to manipulate the vectorial capacity of Anopheles mosquito.